PENGARUH PERMBERIAN HORMON IBA TERHADAP PERTUMBUHAN EKSPLAN DAUN TANAMAN KASTURI (Mangifera casturi) SECARA IN VITRO - Hidayat, Akhmad Noor; Fitriani, Adistina; Payung, Damaris; Syahid, Yulianto; Kristyanto, Sigit (Jurnal Sylva Scienteae, 2024)
Kasturi (Mangifera casturi) is an identity manga plant of South Kalimantan flora that is almost extinct. Kasturi preservation can be done in vitro, which is an efficient species propagation technique. The in vitro method is an aseptic culture of cells, tissues, organs and their components that have the same function and form. This study aims to determine the effect of IBA hormone administration and the right concentration of IBA (Indole Butyris Acid) hormone on the explants of kasturi (Mangifera casturi) leaf growth in vitro. The dose of IBA hormone used is 0.8 mg; 1.0 mg; 1.2 mg; 1.4 mg; and 1.6 mg with 5 replicates each. The results of the study are quantitative data and qualitative data. Quantitative data are the days of callus formation on explants obtained from observations in the laboratory, recorded and recapitulated. As for qualitative data in the form of explant characteristics which include (color, texture, and size) are described based on the results of the study. The results of this study are the use of auxin IBA gives a response to callus growth in kasturi leaf explants (Mangifera casturi) and the fastest concentration of IBA hormone that is appropriate for the growth of kasturi leaf explants is the first treatment with a concentration of 1 gram with the most callus produced, the fastest growth and free from browning